Analisis Kinerja Aparatur Dalam Penyaluran Program Keluarga Harapan (PKH) di Kelurahan Kenangan Baru - Hutabarat, Anjuyto; Lubis, Yurial Arief; Suharyanto, Agung (Universitas Medan Area, 2025)
The Family Hope Program (PKH) is a conditional cash assistance with the target of Very Poor Families (KSM) with the aim of poverty alleviation. This study aims to analyze the performance of government apparatus in distributing PKH to the poor in Kenangan Baru Village and to find out what are the inhibiting factors in the distribution of PKH in the Village. This study focuses on the suboptimal distribution of PKH funds and the inaccuracy of recipient targets. The Mondy, Noe Premeaux theoretical approach is used with indicators of quantity, quality, independence, initiative, adaptation, and cooperation. Data were collected through observation, interviews, and documentation, and then analyzed in a qualitative descriptive manner. This study concludes that the distribution of PKH is going well, but there are still inaccuracies in targets and delays in funding. The apparatus is not yet fully independent, while PKH companions have shown good initiative and adaptation. However, coordination with the village apparatus is still lacking. The main obstacles include data insynchronization, low participation of KPM, limited human resources to accompany them, and undistributed funds.